Esophageal Eosinophilia and Eosinophilic Esophagitis in Celiac Children: A Ten Year Prospective Observational Study - Fernanda Cristofori (MDPI AG, 2021)
The association between eosinophilic esophagitis and celiac disease is still controversial and its prevalence is highly variable. We aimed to investigate the prevalence of esophageal eosinophilia and eosinophilic esophagitis in a large group of children with celiac disease, prospectively followed over 11 years. Methods: Prospective observational study performed between 2008 and 2019. Celiac disease diagnosis was based on ESPGHAN criteria. At least four esophageal biopsies were sampled in patients who underwent endoscopy. The presence of at least 15 eosinophils/HPF on esophageal biopsies was considered suggestive of esophageal eosinophilia; at the same time, eosinophilic esophagitis was diagnosed according to the International Consensus Diagnostic Criteria for Eosinophilic Esophagitis. Results: A total of 465 children (M 42% mean age 7.1 years (range: 1–16)) were diagnosed with celiac disease. Three hundred and seventy patients underwent endoscopy, and esophageal biopsies were available in 313. The prevalence of esophageal eosinophilia in children with celiac disease was 1.6% (95% CI: 0.54–2.9%). Only one child was diagnosed as eosinophilic esophagitis; we calculated a prevalence of 0.3% (95% CI: 0.2–0.5%). The odds ratio for an association between eosinophilic esophagitis and celiac disease was at least 6.5 times higher (95% CI: 0.89–47.7%; p = 0.06) than in the general population. Conclusion: The finding of an increased number of eosinophils (>15/HPF) in celiac patients does not have a clinical implication or warrant intervention, and therefore we do not recommend routine esophageal biopsies unless clinically indicated.